The Effect of Brand Image, Price and Social Media Marketing on Chatime Product Purchasing Decisions - Darmadi, Ravindra Ardiana; Norzianawati, Aishah; Anisa, Friztina; Uliyah, Ida (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
This study aims to test the effect of brand image, price and social media marketing on purchasing decisions. The sample for this research is the public who have made purchases at Chatime. The sampling method used purposive sampling with a total sample of 115 respondents. The analytical tool used is multiple linear regression. The results of this study show that brand image, price and social media marketing have no effect on purchasing decision made by customer.